Selected papers of the "1st International Conference on Nanofluids (ICNf)" - Estellé, Patrice; Hernandez, Leonor; Buschmann, Matthias H. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue of Energies has emerged as a result of the 1st International Conference on Nanofluids (https://icnf2019.com/), which was organized under the auspices of Nanouptake COST Action (Overcoming Barriers to Nanofluids Market Uptake, http://www.nanouptake.eu/) in Castelló (Spain), in June 2019. The foci of ICNf2019 were the production and the characterisation of nanofluids for different areas of applications in the energy fields, namely heat transfer, storage of thermal energy, boiling, and solar systems, as well as industrial applications and health and safety issues. The first conference edition on this topic gathered more than 200 participants from 45 different countries. More than 125 contributions were presented in the nine sections of the congress. Some selected authors were invited to send extended versions of their work to the Energies ICNf2019 Special Issue. After a careful review process, nine articles from six different countries were selected for compilation in this Special Issue: a total of seven full research papers and two reviews. These papers cover a broad range of fundamental and applied research aspects on nanoﬂuid science and development, and reﬂect the current investigations, knowledge, and challenges encountered in the use of nanofluids for energy applications.